2012
DOI: 10.1098/rstb.2011.0219
|View full text |Cite
|
Sign up to set email alerts
|

Social drive and the evolution of primate hearing

Abstract: The structure and function of primate communication have attracted much attention, and vocal signals, in particular, have been studied in detail. As a general rule, larger social groups emit more types of vocal signals, including those conveying the presence of specific types of predators. The adaptive advantages of receiving and responding to alarm calls are expected to exert a selective pressure on the auditory system. Yet, the comparative biology of primate hearing is limited to select species, and little a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 63 publications
1
57
0
Order By: Relevance
“…that differ in their social system provided evidence of a correlation between social complexity and olfactory complexity (Del Barco-Trillo et al, 2012). Lastly, a study on the auditory system of 20 non-human primate species revealed a correlation between social complexity and enhanced hearing sensitivity (Ramsier et al, 2012). This set of comparative studies suggests that the theory of a social-vocal coevolution of communicative abilities might also apply to other communicative modalities at both the production and perception levels (Freeberg et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…that differ in their social system provided evidence of a correlation between social complexity and olfactory complexity (Del Barco-Trillo et al, 2012). Lastly, a study on the auditory system of 20 non-human primate species revealed a correlation between social complexity and enhanced hearing sensitivity (Ramsier et al, 2012). This set of comparative studies suggests that the theory of a social-vocal coevolution of communicative abilities might also apply to other communicative modalities at both the production and perception levels (Freeberg et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…N = 19, Heffner, 2004), the best frequencies for hearing in these species range between 1 and 10 kHz, with a few outliers; in the high frequencies, most primates are able to hear vocalizations ranging up to 35-45 kHz, with prosimians able to hear in much higher frequencies (circa 60 kHz, Ramsier et al, 2012), but humans and chimpanzees limited to lower frequencies (17-29 kHz, Heffner, 2004). Auditory signals are processed similarly in both humans and primates: they are first transformed into neural signals at the basilar membrane of the inner ear, with particular areas of the cochlea sensitive to various frequencies (tonotopy).…”
Section: Vocal Communication: Perceptionmentioning
confidence: 99%
“…This supports evidence from previous analyses indicating that formants higher than F1 correlate more strongly with vocal tract length (GAMBA et al 2012b). Studies of auditory sensitivity by RAMSIER et al (2012;see also RAMSIER et al 2013) have shown that the greatest auditory sensitivity in Eulemur mongoz ranges between 4 and 20 kHz (optimal sensitivity at 8 kHz). This range contains the values of the second and third formants in the vast majority of the vocal types we recorded.…”
Section: Physical Fight Manipulationmentioning
confidence: 93%